Valacyclovir in the Management of Recurrent Intraoral Herpes Infection - Lugito, Manuel DH.; Pradono, Siti A. (UI Scholars Hub, 2014)
Infection by Herpes Simplex Virus (HSV) type I and II cause a worldwide medical problems. HSV-I infections are common in oral and perioral area. After primary infection, HSV becomes latent in the dorsal root ganglia and recurrences are caused by many stimuli. Antiviral agents, prevention of transmission, suppression of recurrences are current management of HSV infection. Objective: to discuss the management of Recurrent Intraoral Herpes (RIH) infection. Case report: a 21 years old female patient came to hospital with irregular painful ulcers in her mouth preceded by prodrome, followed with eruption and outbreak of vesicles. The first laboratory examination confirmed high titer of reactive Immunoglobulin M (IgM) and IgG of anti HSV-I and HSV-II. She was diagnosed to have RIH and treated with oral Acyclovir, multivitamins, immune stimulant and 0.2% chlorhexidine gargle with good healing. Oral Valacyclovir was given after she had another recurrence, with the result of low episodes of RIH and continuous titer improvement of reactive IgM and IgG of anti HSV-I and HSV-II. Conclusion: Oral administration of Valacyclovir as a the oral prodrugs of Acyclovir is effective prophylactic and therapeutic option with many advantages against HSV infection.